Abstract 12754: Is an Induction Test Necessary While Catheter Ablation of Atrial Fibrillation - Sato, Tetsuro; Oikawa, Jun; Fukaya, Hidehira; Kishihara, Jun; Ishizue, Naruya; Saito, Daiki; Matsuura, Gen; Murayama, Yusuke; mitani, yutaro; Niwano, Shinichi; Ako, Junya (Circulation, 2021)
IntroductionIn general, several reports have been that it is beneficial to confirm the induction test of atrial arrhythmias by burst and provide additional procedures after catheter ablation (CA) for atrial fibrillation (AF). However, few reports on whether the presence or absence of an induction test of arrhythmia affects long-term recurrence. HypothesisIn this study, we sought to elucidate the relationship between induction test and recurrence of atrial arrhythmias in patients who underwent CA for AF. MethodsWe enrolled 678 consecutive patients who underwent the first CA for AF from 2014 to 2020. Of all patients, 573 patients (85%) were performed induction test during CA. After propensity score matching with factors that may affect recurrence i.e., age, left atrial diameter, gender, disease type, and history of coronary artery disease, we divided into induction group (n = 104) and non-induction group (n = 104). The primary endpoint was the recurrence of AF and the occurrence of other atrial tachy-arrhythmias after the 90-day blanking period. The observational period was set at one year after the index. ResultsThe median age was 67 (59 - 73) years old with 22% of female. During the periods, the recurrence occurred in 46 (22%) patients. In the log-rank test, there was no significant difference in the recurrence rate between the two groups (P = 0.74). ConclusionsThe induction test might not be required for atrial fibrillation ablation; however, we will need a prospective study in the future.